Effective use of metallic Z-pins for composites' through-thickness reinforcement - M'membe, Beene; Yasaee, Mehdi; Hallett, Stephen; Partridge, Ivana K. (Elsevier, 2019)
Z-pins offer effective through-thickness reinforcement for laminated composites. Various studies have however, shown that metal Z-pins are less effective at bridging Mode I delaminations than carbon-fibre composite Z-pins, due to poor interfacial bonding with the laminate. This is exacerbated by high thermal mismatch between the metallic Z-pins and the laminate. This study investigates inserting metallic Z-pins at angles offset from the laminate normal, to improve the Mode I bridging in composites. The effects on the apparent fracture toughness under pure and mixed Mode I/II loads using single pin specimens is investigated. Results show that, unlike orthogonally inserted metal Z-pins, inclined Z-pins exhibit high energy absorption throughout the mixed mode range. Double Cantilever Beam (DCB) tests show that the inclined metal Z-pins increase the Mode I apparent fracture toughness by a factor of 2 compared to traditional carbon fibre Z-pins. In End Loaded Split (ELS) tests, the Mode II apparent fracture toughness of inclined stainless steel Z-pins, although less than their uninclined equivalent, is greater than that of carbon fibre Z-pins.
Keywords: Fractures toughness; Inclined insertion; Metal Z-pins